2016
DOI: 10.4103/0971-3026.184416
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lesions in dense breasts: Does tomosynthesis help?

Abstract: Context:Mammography in dense breasts is challenging due to lesion obscuration by tissue overlap. Does tomosynthesis offers a solution?Aims:To study the impact of digital breast tomosynthesis (DBT) in characterizing lesions in breasts of different mammographic densities.Settings and Design:Prospective blinded study comparing mammography in two views with Mammography + Tomosynthesis.Methods and Material:Tomosynthesis was performed in 199 patients who were assigned Breast imaging reporting and data system (BIRADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Moreover, DBT displayed structural distortions, microcalcifications, and foci more accu- rately than DM. In this regard, Rangarajan et al reported that DBT is useful in the detection of architectural distortions, visualizing the lesion margins clearly by eliminating tissue overlaps (12).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DBT displayed structural distortions, microcalcifications, and foci more accu- rately than DM. In this regard, Rangarajan et al reported that DBT is useful in the detection of architectural distortions, visualizing the lesion margins clearly by eliminating tissue overlaps (12).…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of this added feature, it is able to unmask the underlying pathology that may be obscured by the superimposed fibro-glandular parenchyma or in other scenarios, confirms the absence of a mass in an apparent density caused by overlapping normal breast tissue on a conventional mammogram (MG). 1 The superimposition of structures can lead to difficulty in assessment of the margins of true masses. During the acquisition of DBT, the X-ray tube moves in an arc (15 to 60 degrees depending upon the sweep angle) over the breast simultaneously acquiring multiple low-dose projections.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of this added feature, it is able to unmask the underlying pathology that may be obscured by the superimposed fibro-glandular parenchyma or in other scenarios, confirms the absence of a mass in an apparent density caused by overlapping normal breast tissue on a conventional mammogram (MG). 1 …”
Section: Introductionmentioning
confidence: 99%
“…The addition of tomosynthesis to 2D mammography has improved cancer detection and decreased false-positive rates ( 20 , 21 ). Furthermore, removing the effects of tissue overlap has made lesion margins more visible and improved lesion characterization ( 22 - 24 ).…”
mentioning
confidence: 99%